Surgical treatment of urinary incontinence in women. Method Kennedy - Bedoya Hevia, M. (2015)
At present the surgical treatment of urinary incontinence in women, is of great importance due to the high percentage of patients attending a specialist, carriers of the disorder. Knowing his great medical and social significance, is that many gynecologists and researchers have delved into his study, where Kennedy one of those who has contributed most to the surgical progress of this disease with its work on the control of urination and They have given sufficient technical basis for effective surgery practice.